Política de educação para jovens e adultos: os desafios para implementação e a manutenção do PMEA no município de Uberlândia-MG (Anos 1980-2000). - Fernandes, Sheila Maria Pereira (2002)
This composition has, like a theme, the Educational Politics of Young People and Adults, trying to get back its history and its principais actions, fowsing the actions ocurred in Uberlândia -MG, from 1982 to 2000, showing its principais challengers of implantation and maintainenc of Municipal Programm for Erradication of Analphabetism (PMEA). Institutional documents statistics data and oral interviews writh ex secretaries, coor-dinators, orientators, teachers and istudents of PMEA were analised and used to support the research. This work is organised in this way: A brief ambraf historie of young and adults education in Brazil, so will show the experi-ences of young and adults education from 1982 to 2000, emphasizing the Municipal Programm for Erradication of Analphabetism (PMEA), showing how it worked during 2000. This resaech analise the young and adults education like a social right, a way to get on a modem society, where man can think by himself, fowsing its importance and chan- ges in order to take righ life quality.